How do laryngeal and respiratory functions contribute to differentiate actors/actresses and untrained voices? - Master, Suely [UNESP]; Guzman, Marco; Josefina Azocar, Maria; Munoz, Daniel; Bortnem, Cori (Elsevier B.V., 2015)
Purpose. The present study aimed to compare actors/actresses's voices and vocally trained subjects through aerodynamic and electroglottographic (EGG) analyses. We hypothesized that glottal and breathing functions would reflect technical and physiological differences between vocally trained and untrained subjects.Methods. Forty participants with normal voices participated in this study (20 professional theater actors and 20 untrained participants). In each group, 10 male and 10 female subjects were assessed. All participants underwent aerodynamic and EGG assessment of voice. From the Phonatory Aerodynamic System, three protocols were used: comfortable sustained phonation with EGG, voice efficiency with EGG, and running speech. Contact quotient was calculated from EGG. All phonatory tasks were produced at three different loudness levels. Mean sound pressure level and fundamental frequency were also assessed. Univariate, multivariate, and correlation statistical analyses were performed.Results. Main differences between vocally trained and untrained participants were found in the following variables: mean sound pressure level, phonatory airflow, subglottic pressure, inspiratory airflow duration, inspiratory airflow, and inspiratory volume. These variables were greater for trained participants. Mean pitch was found to be lower for trained voices.Conclusions. The glottal source seemed to have a weak contribution when differentiating the training status in speaking voice. More prominent changes between vocally trained and untrained participants are demonstrated in respiratory-related variables. These findings may be related to better management of breathing function (better breath support).
Keywords: Actors; Actresses; Voice training; Glottal airflow; Subglottic pressure; Contact quotient